The politics of admission to the teaching career in Mexico: Results of an alleged suitability - Cordero Arroyo, Graciela; Jimenez Moreno, Jose Alfonso (Education Policy Analysis Archives, 2018)
As a consequence of the Mexican Educational Reform of 2013, the educational system allows the entry into teaching in presschools and primary schools to professionals without preservice teacher education, as long as they demonstrate their suitability through two large-scale tests. This article describes and analyzes the implementation of the tests used in the evaluation of admission to the professional teaching service at these educational levels, and in addition, presents empirical evidence of the results of the process of entering the teaching career as a basis to question the alleged suitability in the evaluation results, both nationally and in a federal entity in the northwest of the country. Two references are observed that define the suitability of the teaching performance. The first is an instrument called Profiles, Parameters and Indicators, which serves as a general ideal of what is expected by the teaching function. The second, the standards defined in the measurement process itself. The conclusion addresses the need to review the process of evaluation of the admission to the teaching career in Mexico, as well as to analyze the implications for the devaluation of the teaching profession and the desired educational quality that the entry of professionals without the appropriate training can bring.